Nash equilibria – existence, uniqueness and convergence – in two person non-zero games of timing - Sūdžiūtė, Daina (Lietuvos matematikos rinkinys, 2000)
Special class of Nash equilibria with spectra S1 = S2 = {a,b} is investigated in two person non-zero games of timing.The formulas of the existing and unique equilibria are derived when the kernels satisfy some conditions of monotonicity and boundedness.Possibilities of convergence of sequences of the equilibria when their spectra {an, bn} converge, are surveyd.